Effect of different materials for temporary removable partial denture: an in vitro study on surface roughness and fracture resistance - Almeida, Luiza Oliveira De; Grangeiro, Manassés Tercio Vieira [UNESP]; Figueiredo, Viviane Maria Gonçalves De (Faculdade São Leopoldo Mandic, 2023)
The use of removable partial dentures is considered a common and inexpensive treatment option to rehabilitate edentulous areas. The aim of this study was to evaluate the effect of different materials for provisional removable partial dentures, an in vitro study on surface roughness and fracture resistance. Thermopolymerizable acrylic resin and thermoplastic resin specimens with dimensions of 10 x 10 x 2 mm (blocks) (n=10) and with dimensions of 65 x 20 x 3 mm (bars) (n=10 were analyzed for their surface roughness (Ra) and three-point flexural strength test. All specimens were subjected to oven aging for 60 days at 37°C±0.5°C in distilled water. The statistical analysis was performed with a significance level of 5%, and the surface roughness data were submitted to the Two-way Anova statistical test (P < 0.05) and the mechanical strength data were subjected to One-way Anova statistical test (P < 0.05). For roughness, the factor resin type (P = 0.000) and the factor aging (P = 0.000) were statically significant, as well as showing interaction (P = 0.228). The Thermopolymerizable acrylic resin had the lowest mean roughness values compared to the thermoplastic resin and showed no statistical difference after aging. The same scenario was repeated for flexural strength values; Thermopolymerizable acrylic resin was statistically superior to thermoplastic resin (P = 0.000). Thermopolymerized acrylic resin showed lower surface roughness values and higher flexural strength values compared to thermoplastic resin.

O uso de próteses parciais removíveis é considerado uma opção de tratamento comum e de baixo custo para reabilitar áreas edêntulas. O objetivo deste estudo foi avaliar o efeito de diferentes materiais para próteses parciais removíveis provisórias, um estudo in vitro sobre rugosidade superficial e resistência à fratura. Espécimes de resina acrílica termopolimerizável e de resina termoplástica com dimensões de 10 x 10 x 2 mm (blocos) (n = 10) e de 65 x 20 x 3 mm (barras) (n = 10) foram analisados em rugosidade superficial média (Ra) e teste de resistência à flexão de três pontos. Todos os espécimes foram submetidos ao envelhecimento em estufa por 60 dias a 37 ° C ± 0,5 ° C em água destilada. A análise estatística se deu com nível de significância de 5%, e os dados de rugosidade superficial foram submetidos ao teste estatístico Anova dois fatores (P <0,05) e os dados de resistência mecânica foram submetidos ao teste estatístico Anova um fator (P <0,05). Para rugosidade, o fator tipo resina (P = 0,000) e o fator envelhecimento (P = 0,000) foram estatisticamente significantes, além de apresentar interação (P = 0,228). A resina acrílica termopolimerizável apresentou menores valores médios de rugosidade em relação à resina termoplástica e não apresentou diferença estatística após envelhecimento. O mesmo cenário foi repetido para valores de resistência à flexão; a resina acrílica termopolimerizável foi estatisticamente superior à resina termoplástica (P = 0,000). A resina acrílica termopolimerizada apresentou menores valores de rugosidade superficial e maiores valores de resistência à flexão em relação à resina termoplástica.
Efeito de diferentes materiais para confecção de prótese parcial removível provisória: um estudo in vitro sobre rugosidade superficial e resistência à fratura
Keywords: Dental prosthesis; Flexural strength; Polymers; Prótese dentária; Resistência à flexão; Polímeros